KOMPONEN PENDIDIKAN : DASAR, TUJUAN, DAN IMPLEMENTASI DALAM SISTEM PENDIDIKAN - Bakhrudin All Habsy; Mellaney Karunia Vebrin Wulan; Syah, Bravita Putri; Minnatus Sholihah Ulinnuha (MERDEKA : Jurnal Ilmiah Multidisiplin, 2024)
The components in the education system are a very important and interrelated element, each of these components is for the achievement of an optimal educational goal. These components together form an efficient and effective system that determines the success of the educational process. This research aims to explore a deeper understanding of the components of the education system and a deeper understanding of the interrelationships between the components. This research uses a qualitative method, with the type of literature study. The results of the study will explain (1) what components exist in education, (2) what foundations are used, and (3) how the implementation of educational components in the education system